The Ethics of Homelessness : Philosophical Perspectives - G. John M. Abbarno, (Value Inquiry Book Series ;, 2020)
This new and expanded edition of G. John M. Abbarno's anthology The Ethics of Homelessness underscores what is ignored in plain sight: people without a home or dwelling are also without privacy and dignity. It is argued that they lack moral standing. The chapters uncover the harsh realities of poverty where economic value overrides competing human values. Naomi Zack argues that homelessness is symbolic of society's materialistic values. It has a tendency to resist sufficient charity and perpetuates conditions of injustice. Uma Narayan questions whether the homeless have protection under the U.S. Constitution. Other authors present an enlarged sphere of homeless to include runaway children, refugees, adoptees and the disabled. The book demonstrates the value of applied philosophy.